SYNTHESIS OF TIO 2 NANOPARTICLES AND ANALYSIS OF THEIR TEXTURAL CHARACTERISTICS BY SCANNING ELECTRON MICROSCOPY (World Bulletin of Social Sciences, 2024)
This paper describes a method for synthesizing TiO2 nanoparticles and studying their textural characteristics using scanning electron microscopy. The experiments confirm the efficiency of the chosen synthesis method and provide important data on the morphology, size, and structure of the particles. The study of the textural characteristics of TiO2 nanoparticles has direct implications for their potential use in catalysis, photocatalytic processes, solar cells, and other areas. This work expands our understanding of TiO2 nanoparticles and opens up new prospects for their use in various fields of science and technology
Keywords: morphology; textures; nanoparticle; efficiency